The Effect of Moderate Intensity Continuous Training on V02 Max Overweight Adolescents - Sari Triyulianti; Ayu Permata; Riski Dwi Utami (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aimed to determine the effect of moderate-intensity continuous training (MICT) on V02 Max in overweight adolescents. This study used an experimental method with pre and post-test designs on 20 overweight adolescents according to the inclusion and exclusion criteria. Samples were randomly divided into two groups, the control group and the MICT group. The control group did not do the exercise. The MICT group exercised by running for 30 minutes (64-76% of maximal heart rate), three times per week for four weeks. VO2 Max capacity was measured using a multi-stage fitness test by running back and forth with a 20-meter track. The results showed that there was a significant increase in VO2 max in the MICT group (p=0.00). In the control group, there was a decrease in V02 Max, but there was no significant difference (p=0.869). There was a significant difference in V02 Max between the MICT group and the control group (p=0.005). In conclusion, MICT over four weeks can increase the V02 Max in overweight adolescents.